Peran Kepala Sekolah dalam Pengelolaan Sarana dan Prasarana di Sekolah Dasar - Hanif Ainurrizqi; Nisrina ‘Atifa; Fryzca Sascia Fifiana; Nafisa Paramitha; Lisa Virdinarti Putra (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This article was written with the aim of knowing the role of the principal in managing facilities and infrastructure in Elementary Schools. The subjects used in this article are principals in Elementary Schools. The principal as an educational leader in a school environment, plays an important role or has strategic responsibility for planning, organizing, implementing, and evaluating management in school institutions. This study uses a framework based on the understanding that the principal as a leader and manager at the school level has a central role in managing facilities and infrastructure. Effective management of adequate facilities and infrastructure is believed to create a conducive and effective learning environment, which in turn will improve the quality of the teaching and learning process and student achievement. Adequate and proper facilities and infrastructure are the most important factors in supporting the effectiveness of the teaching and learning process in Elementary Schools. Facilities include everything that supports the learning process directly such as stationery, books, teaching aids, and others while infrastructure includes facilities in Elementary Schools such as classrooms, toilets, teacher rooms, and other places. Therefore, the role of the principal and support from all school residents are needed so that the management of facilities and infrastructure in Elementary Schools is more effective and structured.